Large–scale and high–sensitivity multi–line CO surveys toward the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Enokiya, R.; Torii, K.; Schultheis, M.; Asahina, Y.; Matsumoto, R.; Yamamoto, H.; Tachihara, K.; Okuda, T.; Morris, M. R.; Fukui, Y.
Abstract: We carried out large–scale (4 × 2 degree) CO multi–line observations toward the central molecular zone (CMZ) in the Galactic center (GC) with the NANTEN2 4m telescope and mapped several diffuse molecular features located at relatively high Galactic latitudes above 0°.6. These high–latitude features are composed of diffuse molecular halo gas and molecular filaments according to their morphological aspects. Their high velocities and high intensity ratios between 12 CO J = (2−1) and J = (1−0) clearly indicate their location in the GC, and their total mass amount to ∼10% of that of the CMZ. We discuss that magnetic field is a possible mechanism of these high–latitude molecular features lifting up toward high galactic latitude.